Monitoring the Effects of the Supply Chain Management in South Russia Spatial Socio-Economic System - Violetta V. Rokotyanskaya; Svetlana N. Tsvetcova; Aleksandr Yu. Usanov; Ilya N. Lenkov; Elena L. Kulyakina (International Journal of Supply Chain Management, 2020)
Abstract-The article considers the genesis of monitoring supply chain management effects and describes its types and content, such as socio-economic monitoring, credit monitoring, financial monitoring, taxpayer monitoring and banking monitoring. The monitoring tasks that need to be achieved in order to achieve the goal are defined: continuous monitoring of the state of business processes and obtaining operational information about them; combining information flows generated by different departments of the monitoring enterprise; timely identification of the changes taking place within the process and the factors that caused them; prevention of negative trends; short-term forecasting of the development of critical processes in the enterprise; assessment for the situation for timely decision-making on the planning and implementation of effective activities. The authors proposed and justified a system of indicators, which allows assessing and analyzing the degree of efficiency of development of enterprises of light industry. It included several groups of indicators combined in overall content. On the basis of the available accounting data and additional primary information obtained directly from ten light industry enterprises of the Southern Federal District, a monitoring study of their activities was carried out.